Analisis Kesalahan Siswa dalam Menyelesaikan Soal Higher Order Thinking Skill (HOTS) Berdasar Teori Newman - Murtafiah (LPPM Universitas Advent Indonesia, 2022)
The purpose of this study was to find out the errors and factors that cause errors made by students in solving HOTS questions on the subject matter of a three-variable system of linear equations based on Newman's theory. This study is qualitative research with a case study as the research design. The Subjects in this study is a class XI MIPA 2 SMA Negeri 2 Majene in the academic year 2021/2022, totaling 37 students and 2 students from the high and low ability categories and 1 student from the medium ability category using purposive sampling technique. Instrument of this study were HOTS diagnostic test sheets and interview guidelines. The results of this study indicate that the types of errors made by students in solving HOTS questions on the subject matter of the three-variable system of linear equations are: (1) High ability students make comprehension errors, process skills errors, and encoding errors; (2) medium ability student make comprehension errors, transformation error, process skill error, and encoding errors; (3) low ability students make reading errors, comprehension errors, transformation error, process skill error, and encoding errors . In general, the factors that cause errors are not understanding the meaning of the questions, not being used to writing down things that are known and asked, not careful writing the problem information, difficulty changing the problem into mathematical models, unable to design the solution of the problem properly, not being accustomed to writing conclusion answers, and difficulty compiling sentences in the conclusion of the answer.